Isolation and characterization of microsatellite markers for Cascaria sylvestris Sw. (Salicaceae), a neotropical medicinal tree - Cavallari, M. M. [UNESP]; Billot, C.; Bouvet, J. -M.; Favreau, B.; Zucchi, M. I.; Palmieri, D. A.; Gimenes, M. A. (Blackwell Publishing, 2008)
Casearia sylvestris Sw. is a widespread neotropical tree utilized in popular medicine. Recent research ranked Casearia as one of the most promising genus in the search of drugs against cancer. Despite its wide distribution and pharmacological importance, no microsatellite markers have yet been developed for this genus. In this study, we provide 10 polymorphic microsatellite loci specifically designed for C. sylvestris, used to analyse 90 individuals distributed in two populations from São Paulo state, Brazil. on average, 12.3 alleles per locus were identified, showing the ability of the markers to detect microsatellite polymorphism in this species.
Keywords: Casearia sylvestris; Flacourtiaceae; genetic diversity; microsatellites; molecular markers; Salicaceae